2013
DOI: 10.22605/rrh2492
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for dental caries in small rural and regional Australian communities

Abstract: Introduction: Dental decay (caries) can cause pain, infection and tooth loss, negatively affecting eating, speaking and general health. People living in rural and regional Australian communities have more caries, more severe caries and more untreated caries than those in the city. The unique environmental conditions and population groups in these communities may contribute to the higher caries burden. In particular, some towns lack community water fluoridation, and some have a high proportion of Aboriginal peo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…Although it is hard to know how many of these children brushed twice a day, the figures reported are higher than population data where 56% Aboriginal and Torres Strait Islander children aged 5‐14 years residing in major cities are reported to brush twice or more a day 26 . A recent study involving Aboriginal children in regional NSW also found only half of all children (49%) brushed their teeth more than once a day 31 . Adding to these findings is the fact that nearly all the children owned their own tooth brush which is essential as sharing tooth brushes can increase the risk of developing dental decay due to transmission of bacteria 32 .…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Although it is hard to know how many of these children brushed twice a day, the figures reported are higher than population data where 56% Aboriginal and Torres Strait Islander children aged 5‐14 years residing in major cities are reported to brush twice or more a day 26 . A recent study involving Aboriginal children in regional NSW also found only half of all children (49%) brushed their teeth more than once a day 31 . Adding to these findings is the fact that nearly all the children owned their own tooth brush which is essential as sharing tooth brushes can increase the risk of developing dental decay due to transmission of bacteria 32 .…”
Section: Discussionmentioning
confidence: 89%
“…26 A recent study involving Aboriginal children in regional NSW also found only half of all children (49%) brushed their teeth more than once a day. 31 Adding to these findings is the fact that nearly all the children owned their own tooth brush which is essential as sharing tooth brushes can increase the risk of developing dental decay due to transmission of bacteria. 32 In addition, close to two-thirds of children were using standard toothpaste (62%) at nine years compared to children's toothpaste, a jump of 20% from the previous time point.…”
Section: Discussionmentioning
confidence: 99%
“…In consistent with our findings, the studies conducted by Derikvand et al (2018) and Mahmoudvand et al, (2018) have reported a significant correlation between teeth brushing and the prevalence of E. gingivalis and T. tenax ( Derikvand , 2018 ; Mahmoudvand et al, 2018 ) . Previous studies have reported people living in rural regions poor due to lack of attention to oral health, more frequency of tooth loss and gum diseases was observed ( Zander et al, 2013 ; Chen, 2018 ). Similarly, our findings showed that there was a significant correlation between living in rural regions and the frequency of E. gingivalis and T. tenax; this considerable prevalence in rural communities may be due to some factors such as the low compliance with health standards, lower educational level, more contact between people, and lack of access to health services ( Coughlin et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…38 Despite repeated calls for a focus on social determinants and a common risk factor approach to oral health promotion, 22 , 23 high rates of preventable oral disease remain. 2 , 12 People living in rural and regional Australian communities have more caries, more severe caries and more untreated caries than those in urban areas 4 , 19 , 39 ; they also experience higher rates of potentially preventable hospital admissions due to dental conditions. 6 , 12…”
Section: Discussionmentioning
confidence: 99%